2004
DOI: 10.1007/s00259-003-1448-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second primary cancer following differentiated thyroid cancer

Abstract: Concerns remain over the risk of cancer following differentiated thyroid carcinoma and its causes. Iodine-131 ((131)I) and external irradiation are known to have potential carcinogenic effects. Thyroid carcinoma is a polygenic disease which may be associated with other malignancies. We investigated the incidence of second cancer and its aetiology in a cohort of 875 patients (146 men, 729 women) with differentiated thyroid carcinoma originating from Basse-Normandie, France. Cancer incidence was compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
52
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 17 publications
12
52
2
1
Order By: Relevance
“…In our series, despite the low radioiodine dose, colon carcinoma was developed 9 years after in only one patient with DTC. The other second primary neoplasms were fibrosarcoma, malign fibrous histiocytoma, malign melanoma, renal cell carcinoma, multiple myeloma, breast, colon carcinoma and chronic myelocytic leukemia in agreement with the previous results in the literature [17,18,20]. The most dramatic case in this series (pt no: 11) had a previous history of external radiotherapy due to fibrosarcoma of supraclavicular region at the age of 31.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our series, despite the low radioiodine dose, colon carcinoma was developed 9 years after in only one patient with DTC. The other second primary neoplasms were fibrosarcoma, malign fibrous histiocytoma, malign melanoma, renal cell carcinoma, multiple myeloma, breast, colon carcinoma and chronic myelocytic leukemia in agreement with the previous results in the literature [17,18,20]. The most dramatic case in this series (pt no: 11) had a previous history of external radiotherapy due to fibrosarcoma of supraclavicular region at the age of 31.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies reported an increased risk of second cancers of the genitourinary tract [18][19][20], endocrine glands, nervous system [19], digestive tract, bone and soft tissue [17], salivary gland [17,20] and adrenal gland [20] in patients treated radioiodine for DTC. In the current study, second primary tumors were developed in 9 patients 2-9 years after thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Their data did not support the hypothesis that a significant proportion of double primary cancers are due to hereditary factors. In the present study, we found a standardized incidence ratio of 1.52 (95% CI: 0.46-3.18) for breast cancer comparable with the data published by Berthe et al (4). Moreover, an increased overall incidence (the SIR increases up to 3.95 (95% CI: 2.06-6.45)) for breast cancer in thyroid cancer patients was observed, when taking also the tumors preceding DTC into account.…”
Section: Discussionsupporting
confidence: 77%
“…14,15 Furthermore, in several reported instances, posttreatment WBS has revealed mediastinal 131 I activity that, on subsequent surgical exploration, was found to be attributable to physiologic enlargement of the thymus. 5,16 -20 Without appropriate guidelines, it is difficult to obtain a consensus regarding diagnostic and therapeutic strategies for patients with mediastinal uptake of 131 I.…”
mentioning
confidence: 99%